The Role of Executive Functions in Early Mathematics Achievement: A Cognitive Psychology Perspective - Busnawir Busnawir; Zain Nizam; Nurul Huda (Yayasan Adra Karima Hubbi, 2025)
Early mathematics achievement is a critical predictor of long-term academic success, and understanding the cognitive mechanisms underlying mathematical learning is essential for educational psychology. Executive functions (EF) including working memory, inhibitory control, and cognitive flexibility play a pivotal role in supporting problem-solving, numerical reasoning, and the acquisition of mathematical concepts. This study aims to examine the contribution of executive functions to early mathematics achievement from a cognitive psychology perspective. A mixed-methods approach was employed, combining standardized EF assessments with mathematics performance tests in a sample of children aged 5–7 years. Data were analyzed using correlational and regression techniques to determine the predictive power of specific executive function components. Results indicate that working memory and inhibitory control are strongly associated with early numeracy skills, while cognitive flexibility contributes to adaptive problem-solving in novel mathematical tasks. Children with higher EF scores demonstrated significantly better performance in arithmetic, pattern recognition, and applied problem-solving. The study concludes that integrating EF training into early education curricula could provide a foundation for sustained mathematical competence and cognitive growth.